ANALISIS UPAYA MENINGKATKAN KEMAMPUAN LITERASI MEMBACA SISWA KELAS III SEKOLAH DASAR DI KABUPATEN BLITAR - Mira Triyani; Khanza Islami; Muslih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teachers efforts in improving reading literacy skills of grade III elementary school students in Blitar Regency. The background of this study is based on the low interest and ability of students in reading which is a challenge in fostering a culture of literacy in the Elementary School environment. This study uses a qualitative approach with a descriptive method, with 10 third grade students as research subjects. Data collection techniques were carried out through observation, semi- structured interviews, and documentation, which were analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of the study showed that students' literacy skills were still relatively low, as indicated by the majority of students not having reached the complete category in understanding, concluding, and reflecting on reading. Efforts made by teachers include making reading a habit for 15 minutes every morning, providing a reading corner, and giving assignments to retell the contents of the reading. Supporting factors in the implementation of literacy include parental support, the active role of teachers, and the availability of facilities and infrastructure. Meanwhile, inhibiting factors include low motivation and interest in reading for students, the negative influence of gadgets, and lack of parental involvement. Thus, structured and consistent literacy activities are more effective in improving students' reading literacy skills, especially if supported by elaboration strategies and collaboration between the family and school environments.